PARTISIPASI MASYARAKAT DALAM PROSES PENDAFTARAN TANAH - Yunita Sarah Rosalinda; Fenty Nur Hidayah; Marchanida Firly Nabila (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This research aims to describe community participation in the implementation of the Complete Systematic Land Registration (PTSL) program organized by the National Land Agency in Buton Regency. The study uses a descriptive method with a qualitative approach, involving both primary and secondary data. Informants were selected using purposive sampling, and data collection was carried out through interviews, observations, and documentation. Data analysis included several stages: data preparation, organization, reduction, and presentation. The findings indicate that the PTSL program in Buton emphasizes community involvement in various stages, such as outreach, land registration, boundary determination, and preparing certification requirement documents. Therefore, the government is encouraged to position the community as active participants in the land registration process and support their accountability in this program.